PENDIDIKAN MITIGASI BENCANA GEMPA BUMI MELALUI PEMBELAJARAN BERBASIS PROYEK SIAP STEM - Setyawan, Agung Vendi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
The high risk of earthquake disasters and the unpredictability of their occurrence are the reasons why it is important to increase the understanding of disasters from an early age, especially in the school environment Disaster mitigation education is very important to be implemented in the school environment because it aims to increase students' awareness and skills in dealing with disasters from an early age. Earthquake disaster mitigation education through the application of Simulation, Innovation, Action, Perception (SIAP) project-based learning with a science, technology, engineering, and mathematics (STEM) approach with mock-up products of earthquake-resistant tower buildings made from plastic straws can develop critical thinking skills and collaboration, literacy and numeracy of students. This research is based on best practice with a qualitative approach. Students can develop their skills in designing and creating technology to solve problems, namely the risk of earthquake disasters. The activeness and enth usiasm of students at all stages of learning reached 63.16%. Students' absorption of disaster material through this learning reached 94.21%. Disaster mitigation education aims to ensure that students, especially at the elementary school (SD) level, will create a disaster-resilient generation.